Outlook for Remittance Flows 2011-12 : Recovery After the Crisis, But Risks Lie Ahead - Mohapatra, Sanket; Ratha, Dilip; Silwa, Ani (World Bank, Washington, DC, 2012)
Officially recorded remittance flows to developing countries are estimated to increase by 6 percent to $325 billion in 2010. This marks a healthy recovery from a 5.5 percent decline registered in 2009. Remittance flows are expected to increase by 6.2 percent in 2011 and 8.1 percent in 2012, to reach $374 billion by 2012. This outlook for remittance flows, however, is subject to the risks of a fragile global economic recovery, volatile currency and commodity price movements, and rising anti-immigration sentiment in many destination countries. From a medium-term view, three major trends are apparent: (a) a high level of unemployment in the migrant-receiving countries has prompted restrictions on new immigration; (b) the application of mobile phone technology for domestic remittances has failed to spread to cross-border remittances; and (c) developing countries are becoming more aware of the potential for leveraging remittances and diaspora wealth for raising development finance.